The Contingency Theory of Managerial Accounting: A Reply. - Hayes, David C. (The Accounting Review, 1978)
The article presents the author's reply to the comments made by Associate Professors in Accounting, Peter Tiessen and J.H. Waterhouse on his paper "The Contingency Theory of Managerial Accounting." With respect to the comments on explanatory variables, Tiessen and Waterhouse make a number of points, some of which the author has difficulty in following. As noted by Tiessen and Waterhouse, the budget and financial variables are perceptual in nature; their intent was to elicit perceptual data on the ability of such measures to reflect performance. Interpreting them as inputs or determinants of effectiveness may be stretching a point, but it was difficult to obtain data on relative explanatory abilities in another way. Their second point with respect to the classification of these variables, that there is confusion between an implied surrogation of performance explanators and categorization only as internal variables, indicates confusion on the part of commentators between normative and descriptive statements. With respect to the factor analyses, the points made by Tiessen and Waterhouse are well-taken. The author recognizes, as they do, the problems in its utilization and interpretation.